PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS INKUIRI TERBIMBING PADA MATERI SIFAT- SIFAT CAHAYA KELAS VIII SMP DARUL ULUM 5 JOMBANG - Fina Mafaza; Nur Kuswanti; Oktaffi Arinna Manasikana (Program Studi Pendidikan Fisika FKIP Universitas Samudra, 2019)
Development besed guided inquiry-based sheet of LKS not used at the time of learning, so the students understand the material difficult be learned. The purpose the purpose of this study is to describe the process of developing a guided inquiry-based worksheet that is valid, practical and effective in the material of Light Traits in SMP Darul Ulum 5 Jombang. The development this study uses the development ADDIE. LKS declared eligible based on the results of the validation by the validator Limited trial conducted on 15 students of class VIII A. LKS valida to 4.00, with a very valid criteria At the first meeting the learning outcomes earned an average of 95.5% and 100% second meeting Student responses get 94.81% Student post-pets results 92%. The conclusions of this research is based guided inquiry LKS eligible for use in the learning process the material properties of light in the SMP Darul Ulum 5 Jombang .